(study on extraction of "Gayam" starch). - Siti Sofiah; Murdiati Gardjito (Warta Industri Hasil Pertanian, 1991)
starch was prepared from "Gayam" (inocarpus edulis) seeds in order to increase itsw  shelf life and diversifyb the products.The yield of starch was about 20% the shelled seeds and the degree of gelatinization was 81-85 degree C. Bleaching process affected the corbohydrate content of the starch but not its whitennes.The use of 300 ppm sodium metabisulfite solution decrease the carbohydrate content up to 28.60%.